MACO MAULUD: TRADISI MASYARAKAT INDONESIA KETURUNAN ARAB DI PALEMBANG - Sungkowo Soetopo (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2008)
This article contains the description ofÂ Maco Maulud,Â the tradition of Indonesian society Â of Arab clan in Palembang.Â  Â Maco MauludÂ comes from the wordÂ macoâ€˜readingâ€™ andÂ maulud.Â  Â MauludÂ means â€œbeing born.â€Â  Â Maco-mauludÂ in this case, means reading the history of the Prophet Mohammed existing inMajemuk-Maulid written in Arabic and red like poetry reading or singing.Â  Â There are four maulid scripts inÂ Majemuk-Maulid, maulid ofÂ Syarafal anam,Â maulid of alÂ Barzanji,Â maulid ofÂ Diba,Â and maulid ofÂ Azab. Â Maco maulud,Â made as routine activity for Indone- sian societies of Arab clan. Â It is used as a tradition which almost resembles ritual activities.Â  Â A party, e.g. Â wedding party, and circumcision, are not perfect (afdal) without maco-maulud Â ceremonies.Â Key words:Â maco, maca, maulud, maulid.